Agricultural producers' awareness about the impact of fertilizers overuse on the environment - Panin Biljana; Štrbac Snežana; Pucarević Mira; Stojić Nataša; Žugić-Drakulić Nataša; Prokić Dunja (Agroznanje, 2018)
Overuse of fertilizers can have harmful effects on the environment. The Nitrates Directive aims to protect water quality by preventing nitrates from agricultural sources polluting ground and surface waters and by promoting the use of good farming practices. The paper is based on research about agricultural producers' awareness about the impact of fertilizers overuse on the environment. Data were collected by face to face interviews with farm owners on 39 farms in Serbia. Analysis of the collected data showed that all farmers use fertilizers. It is important to notice that 79.4% of farmers use chemical fertilizers more than recommended, and 87.1% use organic fertilizers more than recommended. Furthermore, 66.6% of farmers do not know specific harmful pollution effects of nitrates on soil and water. 71.7% of farmers have not heard about the Nitrates Directive. Therefore, it can be concluded that farmers are not sufficiently aware of fertilizers impact on the environment and it is necessary to provide education on this.